KONSTRUKSI REALITAS BERITA KABURNYA TAHANAN DAN NARAPIDANA RUMAH TAHANAN SIALANG BUNGKUK PEKANBARU PADA MEDIA ONLINE ANTARARIAU.COM - Ristya Novi Andriani; Belli Nasution (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
In today's digital age everyone easily accesses information through the internet. Nowadays people can know an event somewhere immediately when they search for information through online media. The purpose of this research is to find out the framing and ideology in the news of the escape of prisoners and prisoners of The Prison Sialang Bungkuk Pekanbaru On Online Media Antarariau.com.The method in this research uses qualitative approach with framing analysis method of Robert N. Entman model. Four important elements in the framing analysis of Robert N. Entman's model are Define problems, Diagnose causes, Make moral judgement and Treatment recommendation. The subject in this study is online media covering the escape of prisoners and inmates of Sialang Bungkuk Prison in Pekanbaru in May 2017. Data analysis techniques using Robert N. Entman's framing analysis model.The results found that not all news uploaded in May 2017 there are four elements framing model Robert N. Entman. Antarariau.com the escape of prisoners and inmates of Sialang Bungkuk Pekanbaru Prison as a legal matter. Framing in the news submitted by online media Antarariau.com select sources directly related to the riots. Online media Antarariau.com the Riau Regional Police, the families of detainees, the Ministry of Justice and Human Rights, and legal experts in framing the news.